Home-School Relations International Perspectives (Springer Singapore, 2018)
This book examines new directions in home-school relations from an international perspective. Unlike other current literature that concentrates on traditional models of family-school partnerships in Western countries, it focuses on the contributions of immigrant and minority parents, especially those in Asia and South America. This book brings together international scholars who explore home-school relations in Australia, Brazil, Canada, China, Hong Kong, South Korea, Mongolia, Sweden and the United States.